Anti-theft Security System for Vehicles - Rana, Samir; Mewari, Ritu; Nautiya, Lata (International Journal of Engineering and Technology, 2018)
In todayâ€™s world vehicles form an important asset to us, without which our life would be incomplete. But, when it comes to the security of our vehicles, we are veryÂ helpless. It is of a great concern, especially in metropolitan cities, where these incidents occur each and every day. So, in this paper, I have focussed on the security of vehicles. The setup consists of a mix of software and hardware. In software, I will be using an android application, and in hardware,Â a Raspberry pi board B+ model, a jaw or a gripper and other hardware devices. This whole system will allow you to connect with your vehicle from anytime, anywhere and confirm itâ€™s security. A vehicle is usually the most expensive and important asset next to a home, so this system enables you to keep this asset at your fingertips using wireless technology. Think of it as a wireless leash to your car.Â Â